Ethnomathematical Exploration of The Geometric Structure of The Kepahiang Traditional House - Listri Maya Sari; Winda Ramadianti; Apriza Fitriani (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examines ethnomathematics in the architecture of the Kepahiang Traditional House or Bubungan Lima. Using an ethnographic qualitative approach, this study focuses on identifying mathematical concepts in the physical form, structure, and philosophy of buildings. Data were collected through participatory observation, in-depth interviews with cultural experts, and documentation. The results of the study show that this traditional house is rich in geometric applications, including flat (rectangles, triangles), spatial (limas, cylinders), geometric transformations (reflection, translation, rotation), and lines (parallel, perpendicular) in ornaments and structures. In addition, there was also a traditional body-based measurement system and construction techniques without iron nails that reflected the implicit mathematical understanding of the Rejang people of proportion, precision, and structural strength. All of these findings confirm that ethnomathematics in the Kepahiang Traditional House is a manifestation of local wisdom rich in mathematical meaning. This is highly relevant as a context-based, culture-based learning resource to bridge abstract mathematical concepts while fostering students' appreciation of their local cultural identity.